Thirty-year pediatric residency research and publication productivity: Association with research funding - Nicha Taschanchai (2022)
Background: The Department of Pediatrics, Faculty of Medicine, Ramathibodi Hospital, Mahidol University has developed a residency research program and continuously improved the curriculum. The main source of funds for resident's research projects comes from the Faculty of Medicine. This fund was once limited, but it has been gradually increased. Objective: To assessed publication productivity during the past 30 years and its association with research funding. Materials and Methods: The present study was a retrospective cohort study, using the database containing detailed information on scholarly projects of the Ramathibodi's pediatric residents between 1983 and 2012. Univariate and multivariate analyses of factors that could be associated with publication productivity and types of study design were performed. Results: Three hundred forty-nine projects were included. These projects were categorized into three groups based upon research funding, no fund (F0) (n=255), funded at 50,000 THB or less (F1) (n=67), and funded at more than 50,000 THB (F2) (n=27). The demographic data of residents and mentors among the three groups were not significantly different. A significant increase in the number of publications was positively associated with more funds. The percentage of publications rose with increasing funds (16.5%, 28.4%, and 33.3% in F0, F1, and F2, respectively) (p=0.019). The percentages of the prospective study were also increased with increasing funds (31.4% to 46.3%, and 48.1% in F0, F1, and F2, respectively) (p=0.022). Multivariate analysis demonstrated that funds was the only factor associated with percentage of publications (odds ratio [OR] 2.54, 95% confidence interval [CI] 1.07 to 6.03) and with percentage of prospective study design (OR 7.16, 95% CI 3.50 to 14.66). Funds was an independent factor associated with journal impact factor (adjusted OR 4.09, 95% CI 1.41 to 11.87). Conclusion: An increase in pediatric residency research funding was a major factor associated with an increase in publication productivity.